Research on Automatic Drainage System Technology of Vehicle Gas Storage Cylinder. Issue 4 (May 2019) - Yang, Xiaohu; Zhang, Ting; Zhang, Shimiao
Abstract: In view of the technical problems in the existing technology of the air storage cylinder drainage device in the vehicle braking system, this invention provides an automatic water drainage system for the whole vehicle. An ECU controller is used in this system to control the electromagnetic water drainage valve and sensors to realize intelligent water drainage.